Understanding Degassing Pathways Along the 1886 Tarawera (New Zealand) Volcanic Fissure by Combining Soil and Lake CO2 Fluxes - Hughes, Ery C.; Mazot, Agnes; Kilgour, Geoff; Asher, Cameron; Michelini, Marco; Britten, Karen; Chardot, Lauriane; Feisel, Yves; Werner, Cynthia (Frontiers in Earth Science, 2019)
CO2 flux measurements are often used to monitor volcanic systems, understand the cause of volcanic unrest, and map sub-surface structures. Currently, such measurements are incomplete at Tarawera (New Zealand), which erupted with little warning in 1886 and produced a ∼17 km long fissure. We combine new soil CO2 flux and C isotope measurements of Tarawera with previous data from Rotomahana and Waimangu (regions also along the 1886 fissure) to fingerprint the CO2 source, understand the current pathways for degassing, quantify the CO2 released along the entire fissure, and provide a baseline survey. The total CO2 emissions from the fissure are 1227 t⋅d–1 (742–3398 t⋅d–1 90 % confidence interval), similar to other regions in the Taupō Volcanic Zone. The CO2 flux from Waimangu and Rotomahana is far higher than from Tarawera (>549 vs. ∼4 t⋅d–1 CO2), likely influenced by a shallow silicic body at depth and Okataina caldera rim faults increasing permeability at the southern end of the fissure. Highly localized regions of elevated CO2 flux occur along the fissure and are likely caused by cross-cutting faults that focus the flow. One of these areas occurs on Tarawera, which is emitting ∼1 t⋅d–1 CO2 with a δ13CO2 of −5.5 ± 0.5 ‰, and comparison with previous observations shows that activity is declining over time. This region highlights the spatial and temporal complexity of degassing pathways at volcanoes and that sub-surface structures exert a primary control on the magnitude of CO2 flux in comparison to the surface mechanism (i.e., CO2 released through the soil or lake surface).